Acting wisely in complex clinical situations: 'Mutual safety' for clinicians as well as patients. (2nd December 2021) - Dornan, Tim; Lee, Ciara; Findlay-White, Florence; Gillespie, Hannah; Conn, Richard
Abstract: Purpose: The hope that reliably testing clinicians' competencies would improve patient safety is unfulfilled and clinicians' psychosocial safety is deteriorating. Our purpose was to conceptualise 'mutual safety', which could increase benefit as well as reduce harm. Methods: A cultural-historical analysis of how medical education has positioned the patient as an object of benefit guided implementation research into how mutual safety could be achieved. Results: Educating doctors to abide by moral principles and use rigorous habits of mind and scientific technologies made medicine a profession. Doctors' complex attributes addressed patients' complex diseases and personal circumstances, from which doctors benefited too. The patient safety movement drove reforms, which reorientated medical education from complexity to simplicity: clinicians' competencies should be standardised and measurable, and clinicians whose 'incompetence' caused harm remediated. Applying simple standards to an increasingly complex, and therefore inescapably risky, practice could, however, explain clinicians' declining psychosocial health. We conducted a formative intervention to examine how 'acting wisely' could help clinicians benefit patients amidst complexity. We chose the everyday task of insulin therapy, where benefit and harm are precariously balanced. 247 students, doctors, and pharmacists used a thought tool to plan how best to perform this risky task, given their current clinical capabilities, and in the sometimes-hostile clinical milieus where they practised. Analysis of 1000 commitments to behaviour change and 600 learning points showed that addressing complexity called for a skills-set that defied standardisation. Clinicians gained confidence, intrinsic motivation, satisfaction, capability, and a sense of legitimacy from finding new ways of benefiting patients. Conclusion: Medical education needs urgently to acknowledge the complexity of practice and synergise doctors' and patients' safety. We have shown how this is possible.